Dietary 25-Hydroxyvitamin D3 Supplementation Modulates Intestinal Cytokines in Young Broiler Chickens - Abascal-Ponciano, Gerardo A.; Leiva, Samuel F.; Flees, Joshua J.; Avila, Luis P.; Starkey, Jessica D.; Starkey, Charles W. (Frontiers in Veterinary Science, 2022)
Vitamin D signaling is important for intestinal homeostasis. An increase in vitamin D receptors in immune cells can modulate cell phenotype and cytokine secretion. Cytokines regulate both pro- (interleukin 17; IL-17) and anti-inflammatory (IL-10) responses triggered by external stimuli. Inflammation in intestinal tissues can disrupt the structure and the remodeling of epithelial tight junction complexes, thus, compromising the protective barrier. The objective of the study was to determine the impact of dietary supplementation with 25-hydroxycholecalciferol (25OHD3), a hydroxylated metabolite of vitamin D, on intestinal cytokine abundance and epithelial barrier integrity over time in broilers. A randomized complete block design experiment was conducted to evaluate the effect of dietary 25OHD3 inclusion on relative protein expression of the cytokines, IL-17 and IL-10, and tight junction proteins, Zona Occludens 1 (ZO-1), and Claudin-1 (CLD-1), in broiler chicken duodenum and ileum from 3 to 21 days post-hatch. On day 0, male chicks (n = 168) were randomly assigned to raised floor pens. Experimental corn–soybean meal-based treatments were as follows: (1) a common starter diet containing 5,000 IU of D3 per kg of feed (VITD3) and (2) a common starter diet containing 2,240 IU of D3 + 2,760 IU of 25OHD3 per kg of feed (25OHD3) fed from days 0 to 21. On days 3, 6, 9, 12, 15, 18, and 21, 12 birds per treatment were euthanized to collect tissue samples for quantitative, multiplex, and fluorescent Western blot analysis. Target proteins were quantified using Image Quant TL 8.1 and expressed relative to total protein. Feeding 25OHD3 post-hatch decreased ileal IL-10 (anti-inflammatory) protein expression in 21-day-old broilers compared with VITD3 only (P = 0.0190). Broilers fed only VITD3 post-hatch had greater IL-17 (pro-inflammatory) protein expression in the ileum at 18 and 21 days-of-age (P = 0.0412) than those that fed 25OHD3. Dietary inclusion of 25OHD3 lowered the abundance of key inflammatory cytokines in the ileum of young broilers.